Secure block cipher inspired by the human immune system - Ariffin, Suriyani (2012)
In computer security service, cryptographic algorithm is used to ensure adequate security of the systems or of data transfers. Symmetric encryption block cipher is an important cryptographic algorithm and the quest of enhancing data security is crucial due to the heavy usage of internet and mobile devices worldwide. As stated in the Malaysian National Strategy ICT Roadmap, security is one of the pressing needs and critical infrastructure in Malaysia by 2020. As for Malaysia, it is an advantage if we can develop our own symmetric block cipher for our national security interest. Hence, it is necessary to research a secure symmetric block cipheralgorithm. This thesis proposes to design a secure symmetric encryption block ci- pher inspired by human immune system called the Three Dimensional Advanced Encryption Standard (3D-AES). The thesis identifies the similarity elements and highlights the essential computation elements, namely the antigen-antibody interaction, somantic hypermutation model, Levinthal's paradox, and protein structure that can be applied in symmetric block cipher that fulfills Shannon's confusion and diffusion properties. The empirical findings presented the randomness of the output in the 3D-AES block cipher as compared to the AES block cipher, for the number of iteration rounds reduced by four, from seven to three. The avalanche effect or bit independence analysis has been carried out using correlation coefficient, bit error and key sensitivity in experiments and satisfies the confusion property in non-linearity transformation and sensitivity of the ciphertext generated in the third round of the block cipher. It also measures the diffusion property in linear transformation using branch number in estimating the possible success of differential and linear attacks. There are no three-round linear trails with predictable input-output correlation of above 2-3x34=2-102 and no three-round differential trails with predictable prop- agation ratio of above 2-6x34=2-204 and thus, sufficient to resist differential and linear attacks. It is proven that the 3D-AES block cipher has successfully passed very demanding security analyses and justified that the 3D-AES block cipher is a secure block cipher. Therefore, it will increase the protection of the national information infrastructure and will also contribute as one of a symmetric block cipher in computer security research.